Chemical weathering of sediment (CWS): A web-based application for chemical weathering study of rocks and sediment. (2022) - Babu, Vinay; Rai, Santosh K.; Bhan, Uday; Devaraju, Javaregowda
Graphical abstract: Highlights: Provides an interactive, open-source, user-friendly, cross-platform software solution. Removes the bar of any software installation. Provides a single point, dedicated software solution for calculating chemical weathering indices using major elemental geochemical data of clastic sediments and for producing publication-ready illustrations. Offers complete independence of spreadsheet programs, CorelDraw or similar software for data handling and publication-ready illustrations. Covers various aspects of chemical weathering of clastic sediments exclusively. Abstract: CWS is an open-source application developed for calculating chemical weathering indices using major elemental geochemical data of clastic sediments and for generating associated plots. Chemical weathering indices include Chemical Index of Weathering (CIW), Chemical Index of Weathering without CaO (CIW′; expressed as CIW*), Chemical Proxy of Alteration (CPA), Chemical Index of Alteration (CIA), Plagioclase Index of Alteration (PIA), Modified Chemical Index of Alteration (CIX), Index of Compositional Variability (ICV) and Weathering Index of Parker (WIP). Also, hierarchical charts, histogram, boxplots, scatter matrices, correlation matrices, heatmap with related data tables are included along with the statistical measures of weathering indices and their correlation with Al2 O3 /TiO2 . Additionally, it generates plots of input data used to quantify chemical weathering of clastic sediments in various compositional space diagrams, such as A - CN - K, A - CNK - FM and M - F - W compositional space diagram. Using CWS, one can do all the calculations and artwork associated with the finished report without having to use Microsoft Excel, CorelDraw or similar software. Input data source files and output calculations results data files are both in CSV format (Comma Separated Value). HTML files can be exported for plots generated by CWS. As an example of the capability of CWS to evaluate chemical weathering, we evaluated Surma and Barail sandstones from the Mizoram Foreland Basin in North-eastern India, Manasbal Lake sediments from Kashmir; channel, suspended and overbank sediments of the Peninsular rivers of Ganga basin.